Regulation of expression of human IL-1 alpha and IL-1 beta genes. - Turner, M; Chantry, D; Buchan, G; Barrett, K; Feldmann, M (1989)
IL-1 gene expression was investigated in human blood mononuclear cells. IL-1 alpha and IL-1 beta mRNA were induced with LPS or TNF. Kinetic measurements on Northern blots revealed that these stimuli elicited qualitatively similar changes in IL-1 mRNA levels, and that expression of IL-1 mRNA was transient. IL-1 beta mRNA was the predominant mRNA species and remained elevated for somewhat longer than IL-1 alpha mRNA. TNF and IFN-gamma synergized to induce both species of IL-1 mRNA and IL-1 bioactivity. Transcriptional control, as measured by nuclear run on assays, partly determines the greater levels of IL-1 beta mRNA because the rate of IL-1 beta transcription was greater than that of IL-1 alpha. Cycloheximide (CHX) was able to induce IL-1 mRNA but did not induce transcription of either IL-1 gene. When added to cultures pretreated with TNF or LPS, CHX superinduced IL-1 mRNA, but IL-1 transcription was not increased. If added simultaneously CHX blocked TNF-induced IL-1 gene transcription, suggesting that TNF may induce factors required for IL-1 gene transcription. CHX increased the stability of both IL-1 alpha and IL-1 beta mRNA, demonstrating the existence of a post-transcriptional form of control. In half-life experiments IL-1 beta mRNA was more stable than IL-1 alpha mRNA, indicating that post-transcriptional control also contributes to the greater steady state levels of IL-1 beta. Taken together, the available evidence suggests IL-1 alpha and IL-1 beta mRNA are regulated differentially at both the transcriptional and post-transcriptional level.